Myocardial Injury and Cardiac Reserve in Patients With Heart Failure and Preserved Ejection Fraction - Obokata, Masaru; Reddy, Yogesh N V; Melenovsky, Vojtech; Kane, Garvan C; Olson, Thomas P; Jarolim, Petr; Borlaug, Barry A (Journal of the American College of Cardiology, 2018)
BACKGROUND: Cardiac reserve is depressed in patients with heart failure and preserved ejection fraction (HFpEF). The mechanisms causing this are poorly understood. OBJECTIVES: The authors hypothesized that myocardial injury might contribute to the hemodynamic derangements and cardiac reserve limitations that are present in HFpEF. Markers of cardiomyocyte injury, central hemodynamics, ventricular function, and determinants of cardiac oxygen supply-demand balance were measured. METHODS: Subjects with HFpEF (n = 38) and control subjects without heart failure (n = 20) underwent cardiac catheterization, echocardiography, and expired gas analysis at rest and during exercise. Central venous blood was sampled to measure plasma high-sensitivity troponin T levels as an index of cardiomyocyte injury. RESULTS: Compared with control subjects, troponins were more than 2-fold higher in subjects with HFpEF at rest and during exercise (p < 0.0001). Troponin levels were directly correlated with left ventricular (LV) filling pressures (r = 0.52; p < 0.0001) and diastolic dysfunction (r = -0.43; p = 0.002). Although myocardial oxygen demand was similar, myocardial oxygen supply was depressed in HFpEF, particularly during exercise (coronary perfusion pressure-time integral; 44 ± 9 mm Hg × s × min-1 × l × dl-1 vs. 30 ± 9 mm Hg × s × min-1 × l × dl-1; p < 0.0001), and reduced indices of supply were correlated with greater myocyte injury during exercise (r = -0.44; p = 0.0008). Elevation in troponin with exercise was directly correlated with an inability to augment LV diastolic (r = -0.40; p = 0.02) and systolic reserve (r = -0.57; p = 0.0003), greater increases in LV filling pressures (r = 0.55; p < 0.0001), blunted cardiac output response (r = -0.44; p = 0.002), and more severely depressed aerobic capacity in HFpEF. CONCLUSIONS: Limitations in LV functional reserve and the hemodynamic derangements that develop secondary to these limitations during exercise in HFpEF are correlated with the severity of cardiac injury, assessed by plasma levels of troponin T. Further study is warranted to determine the mechanisms causing myocyte injury in HFpEF and the potential role of ischemia, and to identify and test novel interventions targeted to these mechanisms. (EXEC [Study of Exercise and Heart Function in Patients With Heart Failure and Pulmonary Vascular Disease]; NCT01418248).
Keywords: senioři; Stroke Volume; senioři nad 80 let; Male; cvičení; nemoci koronárních tepen; exercise; poranění srdce; Middle Aged; mužské pohlaví; troponin T; studie případů a kontrol; tepový objem; Coronary Artery Disease; Aged, 80 and over; kyslík; hemodynamics; ženské pohlaví; Humans; Troponin T; HFpEF; lidé středního věku; srdeční selhání; Heart Injuries; Exercise; Oxygen; Female; Aged; biomarkers; heart failure; Heart Failure; lidé; Case-Control Studies